Strategi Pembina Asrama Menanamkan Kedisiplinan Siswa Dalam Shalat Berjamaah di Pondok Pesantren Nurul Yaqin Siti Manggopoh Kecamatan Lubuk Basung Kabupaten Agam - Nesi Alia Pitri; Jasmienti Jasmienti; Alimir Alimir; Nurhasnah Nurhasnah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to describe the strategies of dormitory caregivers in fostering the morals of students at the Nurul Yaqin Siti Manggopoh Islamic Boarding School, Lubuk Basung District, Agam Regency. Through this type of research that uses a qualitative descriptive approach that explains the strategy of dormitory caregivers in fostering the morals of students at Pondok Pesantren Nurul Yaqin Siti Manggopoh Kecematan Lubuk Basung, Agam Regency. and observation for supporting data from interview results. The results of this study indicate that: first, the strategy of the hostel supervisor instills student discipline in congregational prayers at the Nurul Yaqin Siti Manggopoh Islamic Boarding School: a. the hostel supervisor makes rules in congregational prayers. b the supervisor of the hostel gives sanctions or punishments in congregational prayers. c the hostel supervisor gives a warning or reprimand. second, the obstacles faced by students so that they are negligent in carrying out congregational prayers at the Nurul Yaqin Siti Manggopoh Islamic Boarding School a. lack of facilities and infrastructure in the dormitory b. low student interest in carrying out congregational prayers c. lack of firmness within students to refuse friends' invitations not to pray congregation.